Mass Cytometry Reveals the Imbalanced Immune State in the Peripheral Blood of Patients with Essential Hypertension - Rui Yang; Yuhong He; Honggang Zhang; Qiuju Zhang; Bingwei Li; Changming Xiong; Yubao Zou; Bingyang Liu (Cardiovascular Therapeutics)
Mounting evidence has confirmed that essential hypertension (EH) is closely related to low-grade inflammation, but there is still a lack of in-depth understanding of the state of immune cells in the circulating blood of patients with EH. We analyzed whether hypertensive peripheral blood immune cell balance was destroyed. The peripheral blood mononuclear cells (PBMCs) of all subjects were analyzed using time-of-flight cytometry (CyTOF) based on 42 kinds of metal-binding antibodies. CD45+ cells were categorized into 32 kinds of subsets. Compared with the health control (HC) group, the percentage of total dendritic cells, two kinds of myeloid dendritic cell subsets, one intermediate/nonclassical monocyte subset and one CD4+ central memory T cell subset in the EH group, was significantly higher; the percentage of low-density neutrophils, four kinds of classical monocyte subsets, one CD14lowCD16- monocyte subset, one naive CD4+ and one naive CD8+ T cell subsets, one CD4+ effector and one CD4+ central memory T cell subsets, one CD8+ effector memory T cell subset, and one terminally differentiated γδ T cell subset, decreased significantly in EH. What is more, the expression of many important antigens was enhanced in CD45+ immune cells, granulocytes, and B cells in patients with EH. In conclusion, the altered number and antigen expression of immune cells reflect the imbalanced immune state of the peripheral blood in patients with EH.